ChemInform Abstract: Carbonate‐Bridged Lanthanoid Triangles: Single‐Molecule Magnet Behavior, Inelastic Neutron Scattering, and ab initio Studies. Issue 32 (22nd July 2016) - Giansiracusa, Marcus J.; Vonci, Michele; Van den Heuvel, Willem; Gable, Robert W.; Moubaraki, Boujemaa; Murray, Keith S.; Yu, Dehong; Mole, Richard A.; Soncini, Alessandro; Boskovic, Colette
Abstract: Compounds (IV) are characterized by single crystal XRD, magnetic measurements, inelastic neutron scattering, and CASSCF ab initio calculations.